MOTIVATION OF DEATH IN VASYL STEFANYK’S CREATIVITY - Наконечна, Л. Б.; Наконечна-Роганіна, Л. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the theme of death in novellas by Vasyl Stefanyk. The motivation of death its mythopoetic nature is analyzed. The invariant of a death motif in Vasyl Stefanik’s art world is revealed. The authors also focus on a number of transformations of the death motif and its correlation with other motives.